2022
DOI: 10.3390/jof8070695
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis of Low-Temperature Fruiting Highlights the Promising Cultivation Application of the Nutrients Accumulation in Hypsizygus marmoreus

Abstract: Hypsizygus marmoreus is a representative edible mushroom with low-temperature fruiting after a long postripening (LFLP). Clarifying the mechanism of LFLP and applying a rigorous low-temperature-limited process will optimize the mushroom cultivation process. This study performed an integrative multi-omics analysis of the molecular mechanism of LFLP in combination with genetic, physiological, and cultivation confirmation. The results showed that the amino acid content was increased during LFLP, mainly arginine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Whether phosphoribosyl is a key signaling factor for the mature mycelial needs further research. The content of arginine in the substrate of H. marmoreus has been reported to increase as the mycelium culture time increases, and the addition of arginine shortens the postripening period and increases the fruiting body yield ( Gong et al, 2022 ). The external addition of arginine influences the rate of development Sordaria macrospora Auersw ( Molowitz and Hock, 1976 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether phosphoribosyl is a key signaling factor for the mature mycelial needs further research. The content of arginine in the substrate of H. marmoreus has been reported to increase as the mycelium culture time increases, and the addition of arginine shortens the postripening period and increases the fruiting body yield ( Gong et al, 2022 ). The external addition of arginine influences the rate of development Sordaria macrospora Auersw ( Molowitz and Hock, 1976 ).…”
Section: Discussionmentioning
confidence: 99%
“…The long cultivation period provides an opportunity for contamination and severely limits industrialized production. Multi-omics analysis has shown that the contents of arginine and citrate in the substrate are key factors in the postripening period ( Gong et al, 2022 ). However, it is not clear why H. marmoreus requires such a long postripening time; thus, it is essential to understand the life cycle of this mushroom.…”
Section: Introductionmentioning
confidence: 99%
“…Another study corroborated the longchain fatty acid synthesis pathway which was responsible for stipe gradient elongation in F. filiformis [9]. Gong et al offered a novel strategy of Hypsizygus marmoreus cultivation using vernalization-like low-temperature fruiting [10]. Li et al speculated the horizontal transfer of functional 1-aminocyclopropane-1-carboxylate oxidase via analyzing phylogenesis [11].…”
mentioning
confidence: 84%
“…Organic acid metabolism is of great significance at the cellular level in several biochemical pathways, including energy production, the formation of amino acid biosynthetic precursors, and regulation of the level of plant adaptation to the environment [ 19 ]. It has been found that the exogenous addition of citric acid shortened the postripening period and increased the fruiting body yield of Hypsizygus marmoreus by enhancing the activity of the TCA cycle [ 20 ]. Citric acid promotes growth, is involved in energy metabolism as an intermediate metabolite in the TCA cycle, and also acts as a precursor for lysine biosynthesis, implying a potentially important role in the improvement in quality of F. filiformis .…”
Section: Introductionmentioning
confidence: 99%